UZUN TUMANI LANDShAFTLARINING TAVSIFI VA ULARNI KARTALAShTIRISh MASALALARI - Mingaliyev, R.O. (SCIENCE and SOCIETY, 2025)
As a result of the increase in the world’s population and the scale of their use of nature, the impact of humanity on nature is increasing. In the Uzun district of Surkhandarya region, where the geoecological situation is deteriorating due to environmental problems such as degradation of mountain pastures, ravines, and soil erosion, a comprehensive, holistic study of nature and a systematic approach to finding solutions to the emerging problems are important. The use of a landscape approach in rational use of natural resources and finding solutions to environmental problems helps to obtain practical results. Historical-evolutionary, genetic and structural principles, as well as a multi-level scheme developed by V.A.Nikolaev, were used to determine the boundaries and classification of the landscapes of the Uzun district. GAT technologies were used to map the landscapes of the Uzun district. As a result of the study, the following landscape units were distinguished and identified in the territory of the Uzun district: 1 class, 3 species, 7 categories, and 13 landscape types.